Increased ACE2, sRAGE, and Immune Activation, but Lowered Calcium and Magnesium in COVID-19 - Al-Hakeim, Hussein K.; Al-Jassas, Hawraa Kadhem; Morris, Gerwyn; Maes, Michael (Recent Advances in Inflammation & Allergy Drug Discovery, 2022)
Background: The characterization of new biomarkers that could help externally validate the diagnosis of COVID-19 and optimize treatments is extremely important. Many studies have established changes in immune-inflammatory and antibody levels, but few studies measured the soluble receptor for the advanced glycation end product (sRAGE), angiotensin-converting enzyme 2 (ACE2), calcium, and magnesium in COVID-19. Objective: To evaluate serum advanced glycation end-product receptor (sRAGE) and angiotensin converting enzyme (ACE)2 and peripheral oxygen saturation (SpO2) and chest CT scan abnormalities (CCTA) in COVID-19. Methods: sRAGE, ACE2, interleukin (IL)-6, IL-10, C-reactive protein (CRP), calcium, magnesium, and albumin were measured in 60 COVID-19 patients and 30 healthy controls. Results: COVID-19 is characterized by significantly increased IL-6, CRP, IL-10, sRAGE, ACE2, and lowered SpO2, albumin, magnesium, and calcium. COVID-19 with CCTAs showed lower SpO2 and albumin. SpO2 was significantly inversely correlated with IL-6, IL-10, CRP, sRAGE, and ACE2, and positively with albumin, magnesium, and calcium. Neural networks showed that a combination of calcium, IL-6, CRP, and sRAGE yielded an accuracy of 100% in detecting COVID-19 patients, with calcium being the most important predictor followed by IL-6 and CRP. Patients with positive IgG results showed a significant elevation in the serum level of IL-6, sRAGE, and ACE2 compared to the negatively IgG patient subgroup. Conclusion: The results show that immune-inflammatory and RAGE pathways biomarkers may be used as an external validating criterion for the diagnosis of COVID-19. Those pathways coupled with lowered SpO2, calcium, and magnesium are drug targets that may help reduce the consequences of COVID-19.
Keywords: COVID-19